Kőrösi Csoma Sándor utazásai, tudományos életműve és hatása a földrajz nézőpontjából - Kubassek, János (Modern Geográfia, 2022)
Many disciplines consider the oeuvre of Alexander Csoma de Kőrös as belonging to their field of expertise. His scholarly achievements are indeed related to linguistics, oriental studies, Tibetology, Indology as well as the history of religion, and Buddhism. Csoma de Kőrös’s interest in the original homeland of Hungarians was aroused by the articles of Ézsaiás Budai, György Pray and the lectures of Professor Blumenbach from the University of Göttingen. He mastered the Tibetan language and, using Tibetan literature hitherto unknown to European scholars, as well as his personal travel experience, he wrote a dissertation entitled “Land Survey of Tibet in Accordance with Tibetan Sources.” The paper contains important data on the characteristics of the Tibetan provinces discussing their economy and environment, as well as their mineral resources, rivers, lakes, and glaciers. Alexander Csoma de Kőrös had a significant intellectual influence on Hungarian geographers. Lajos Lóczy, Ervin Baktay, Jenő Cholnoky, László Kádár and Dénes Balázs all greatly valued his work. The Hungarian Geographical Society immortalized its memory with a laudatory medal. His statue was erected in the garden of the Hungarian Geographical Museum in 1984.